Accuracy of transcutaneous bilirubin level measured by a JM-105 bilirubinometerKey note - Akira Ohishi; Miyuki Kondo; Tomoka Fujita; Toru Baba; Shigeo Iijima (Elsevier, 2023)
Background: Transcutaneous bilirubin (TcB) measurement is useful, but dissociation with total serum bilirubin (TSB) is a clinical problem in measurement. We verified the accuracy of the latest version of the JM-105 jaundice meter. Methods: The TcB, TSB, and hematocrit (Hct) measurements obtained in the first 4 days of life in 2788 term neonates were analyzed. Results: When divided into 2-mg/dL classes, the difference between the TcB and TSB measurements did not change as TcB increased, but both overestimation and underestimation of TcB increased as TcB increased. At TcB greater than 11 mg/dL, inaccurate measurements with dissociation greater than 2 mg/dL exceeded 10% of the TcB measurements. The Hct value was associated with overestimation and underestimation. Conclusion: To evaluate neonatal jaundice accurately, it is desirable to measure TSB by blood sampling before discharge from obstetrics or in the case of worsening jaundice on day 4 or 5 of life.